2021
DOI: 10.1111/ijcp.14402
|View full text |Cite
|
Sign up to set email alerts
|

Immediate retrograde amnesia induced by midazolam: A prospective, non‐randomised cohort study

Abstract: Midazolam, a short-acting benzodiazepine, has sedative, hypnotic, anxiolytic, amnestic and anticonvulsant effects. Given its advantages of rapid onset, short duration and low toxicity, midazolam is optimal for any procedural sedation. 1,2 The communication between healthcare providers and patients does not seem to be affected even with the use of midazolam in some cases; however, anterograde amnesia is beneficial in conscious sedation as it reduces unpleasant memories before or during the surgery. 3 The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Benzodiazepine is associated with retrograde amnesia for a brief period and with respect to visual and event memory. [ 9 ] Thus, we evaluated retrograde amnesia as a secondary endpoint. Additionally, when remimazolam is used in future endoscopy examinations at outpatient clinics, time to full awakening (as a safety evaluation) may be an indicator of length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepine is associated with retrograde amnesia for a brief period and with respect to visual and event memory. [ 9 ] Thus, we evaluated retrograde amnesia as a secondary endpoint. Additionally, when remimazolam is used in future endoscopy examinations at outpatient clinics, time to full awakening (as a safety evaluation) may be an indicator of length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the cutoff for age was defined at <65 years. Benzodiazepine is associated with retrograde amnesia for a brief period and with respect to visual and event memory [9] . Thus, we evaluated retrograde amnesia as a secondary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the retention of preoperative memories was preserved in all patients after anesthesia with either remimazolam or propofol. It has been reported that midazolam (0.1 mg/kg) was associated with retrograde amnesia for a brief period regarding visual and event memory in patients undergoing caesarean delivery with spinal anesthesia [ 18 ]. The overall retrograde card recall rate was lower in the midazolam group compared with the control (no-sedatives) group (77.0 ± 13.4 vs. 87.7 ± 3.9%, p < 0.001), especially at 1 min before midazolam administration (58% vs. 88%, p < 0.001) in non-RCT setting.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde or anterograde amnesia are defined as a loss of memory about events which is acquired before or after the incidents that caused the amnesia. Previous reports show that retrograde or anterograde amnesia occur after general anesthesia in humans ( Aulakh et al, 2018 ; Gruber and Reed, 1968 ; Koht and Moss, 1997 ; Quraishi et al, 2007 ; Sohn et al, 2021 ; Twersky et al, 1993 ) and rodents ( Dutton et al, 2002 , 2001 ; Gerlai and McNamara, 2000 ; O'Gorman et al, 1998 ). However, the underlying mechanism of anesthesia-induced amnesia remains unclear.…”
Section: Introductionmentioning
confidence: 97%